Photo-Fenton Degradation of RB5 Dye in Aqueous Solution Using Fe Supported on Mexican Natural Zeolite. (21st November 2019) - Domenzain-Gonzalez, José; Castro-Arellano, José J.; Galicia-Luna, Luis A.; Lartundo-Rojas, Luis
Abstract : A Mexican natural zeolite (MNZ) was impregnated with Fe at concentrations of 5 and 10 mg FeCl3 /g MNZ (MNZ/Fe) in order to study the photo-Fenton degradation of Reactive Black 5 (RB5) dye. Two samples were prepared and calcined at 550 and 700°C for each concentration. These samples were also characterized by the following techniques: X-ray diffraction (XRD) to determine crystalline phases of mineral, X-ray photoelectron spectroscopy (XPS) to observe the elemental composition of the material where the main element was Fe as Fe2p, Mössbauer to establish the phases in the material which were magnetite (Fe3 O4 ), fayalite, and chlorite, Raman to corroborate that magnetite clusters in natural material were presented, and transmission electron microscopy (TEM) by which magnetite nanoparticles were observe on zeolite surface. Afterwards, the catalytic degradation of RB5 dye was performed by photo-Fenton process using a 2.2 W lamp as a radiation source. Four initial concentrations of RB5 dye ((RB5)0 ) were evaluated which ranged from 40 to 100 mg/L. Then, the evaluation reaction was carried out by UV-Vis spectroscopy to know the change in RB5 concentration and chemical oxygen demand (COD) removal to determine the organic carbon. The best results on the photo-Fenton degradation was 91% discoloration and 68.5% chemical oxygen demand removal based on an initial concentration RB 5 0 = 100 mg/L and 10 mg MNZ/Fe (700°C of calcined temperature) at MNZ / Fe = 0.05 g/L catalyst dose in aqueous solution, H 2 O 2 = 3 g/L, pH = 2.5, and 180 minutes of reaction time. Subsequently, variations on (RB5)0, pH, (H2 O2 ), and (MNZ/Fe) were assessed in order to optimize the process by keeping 10 MNZ/Fe. The optimal RB5 dye degradation was achieved at RB 5 0 = 100 mg/L in the presence of MNZ / Fe = 0.2 g/L, H 2 O 2 = 3 g/L and pH = 2.5 where the highest discoloration and chemical oxygen demand removal were 93 and 70.5 at 180 min. Finally, the kinetic reaction was evaluated as a pseudo-first-order kinetics with an apparent rate constant ( k app ) of 0.0225 min -1 at latest conditions.